TAX PAYMENTS DETERMINANTS IN ROMANIA - Lazar Sebastian (Annals of the University of Oradea: Economic Science, 2015)
Using a fixed effects panel data estimation model in order to account for individual firm heterogeneity, the paper investigates the determinants of corporate tax payments for Romanian non-financial companies listed at Bucharest Stock Exchange over twelve years period (2000 – 2011), adopting a new approach, the natural logarithms of corporate income taxes actually paid as dependent variable. This removes the inherent flaws of firm specific effective tax rates, while establishing a more comparable field for subsequent similar research. All the determinants investigated were found as having an impact, albeit at different level of significance. Capital intensity, leverage and labour intensity were found as having a negative effect, while profitability and size have a positive impact. The findings correspond in general to conventional theory. Moreover, the paper produces evidence concerning the impact of loss carry-forward provisions on firm tax payments.